Pseudo progression in heterogeneity of right-sided metastatic colon carcinoma during nivolumab therapy: A case report. Issue 32 (August 2019) - Wang, Jing; Zhen, Wei; Kang, Xindan
Abstract: Rationale: Pseudo progression is a noted phenomenon of immune checkpoint inhibitors therapy, which has been defined as a response after an initial enlargement of the tumor followed by tumor reduction. In July 2017, the Food and Drug Administration granted accelerated approval of nivolumab for the treatment of metastatic colorectal cancer patients whose tumor harbors deficient mismatch repair. Patient concerns and diagnosis: We present a patient who received nivolumab for heterogeneity of right-sided metastatic colon carcinoma. Intervention: The patient was treated with nivolumab combined with chemotherapy. Outcome: The computed tomography showed mass lesion in the left lobe of liver remained stable while metastasis tumors under envelop of liver were exacerbated after 6 cycles of nivolumab combined with chemotherapy, and later regressed. Lessons: The status of mismatch repair in primary tumor and metastatic liver carcinoma is contradictory but using nivolumab demonstrated encouraging efficacy. This is the first case of pseudo progression undergoing immunotherapy for heterogeneity of right-sided metastatic colon carcinoma.